MODEL PENGAWASAN DAN EVALUASI PENDIDIKAN : STRATEGI PENGAWASAN DAN EVALUASI UNTUK MENINGKATKAN KINERJA KELEMBAGAAN PESANTREN BERKEMBANG - Moh.Robi’al Muhasibi; M Shidiq Purnomo (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This study examines a model of educational supervision and evaluation as a strategic approach to enhancing institutional performance in developing pesantren. The urgency of this research lies in the need for developing pesantren to implement structured supervision and evaluation systems in order to ensure effective governance, educational quality, and institutional accountability amid social and educational policy changes. This research employs a qualitative method with a library research approach by analyzing literature on educational management, supervision, evaluation, and pesantren governance. The discussion focuses on concepts, principles, and models of supervision and evaluation relevant to the characteristics of developing pesantren, including internal supervision, performance evaluation, and institutional leadership roles. The findings indicate that systematic supervision and evaluation function as mechanisms for quality control, continuous improvement, and the strengthening of organizational culture within pesantren institutions. The implications of this study highlight that the implementation of adaptive and contextual supervision and evaluation models contributes to improved institutional performance of developing pesantren in managerial, academic, and Islamic educational value dimensions.